Risk factors for end stage renal disease in children with anorectal malformation and outcome comparison to children with isolated urological anomalies. Issue 6 (December 2022) - Duci, Miriam; Fascetti Leon, Francesco; Castagnetti, Marco; Benetti, Elisa; Meneghesso, Davide; Gaspari, Tommaso; Gamba, Piergiorgio; De Corti, Federica
Summary: Background: End stage renal disease (ESRD) requiring kidney transplant (KT) remains an important cause of morbidity in anorectal malformations (ARM) patients. Current literature is scarce on defining the risk factors for ESRD and the outcomes of KT in ARM patients. Objective: This study aimed to identify predisposing factors to ESRD in ARM patients and verify if the long term outcome of KT in these patients differs from pure urological anomalies (UA). Study design: Databases of ARM and KT patients treated at our center between 2000 and 2016 were used for comparing characteristics of ARM cases which developed ESRD and those who did not, and the outcome features of MAR-KT vs UA-KT. Results: Out of 117 ARM patients, 9 developed ESRD. All of them had a complex ARM. Association with UA were significantly higher in ARM-KT compared to other ARM patients (100% vs. 52%, p = 0.001). The most common UA associated to KT in ARM patients was renal dysplasia. During the same period 23 patients underwent KT as a sequelae of pure urological anomalies (UA-KT group). The most represented UA were primary vesico-ureteral reflux (65.2%) and posterior urethral valves (14%) in UA-KT (table 2). ARM-KT patients required more often hemodialysis before KT (50% vs. 8.7%, p = 0.05) and an aorto-caval anastomosis at the transplant (75% vs. 30%, p = 0.04) compared to UA-KT. Moreover ARM-KT patients experienced more often graft failure and and the need for a second KT (50% vs. 8.6%, p = 0.02). Discussion: To our knowledge, this is the first study describing the differences in terms of risk factors and outcomes of KT in ARM patients. We observed a need for KT in 7% of ARM, which is at the higher end of the range reported in the literature. Bilateral dysplasia and cloaca malformation seem the leading cause to ESRD for ARM patients compared to vesico-ureteral reflux and posterior urethral valve in UA-KT. Our experience showed that KT has worst outcome in ARM vs pure UA patients. Conclusion: Patients with complex ARM are more frequently associated to renal dysplasia which lead to KT. Graft in ARM patients seems to be the more vulnerable and prone to failure.